PENGARUH LINGKUNGAN KELUARGA TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X IIS SMA NEGERI 1 PANGEAN - Jasmira, Jasmira; Suarman, Suarman; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
English abstract: The aim of this research is to determine the influence of family environment toward students’ learning motivation in economic subject class X IIS SMA Negeri 1 Pangean. The research’s population is all the sample 79 students. The data was taken by questioners and analyzed by linear regression. Based on the result is known that students’ family environment is not good. Meanwhile, students’ motivation some of them is low category. The result analysis data was gotten that family environment has positive influenced and significant towards students’ learning motivation contribution is 27,4%. It means that to increase the students’ learning motivation is needed good and conducive family environment. As better and espouse family environment so as better to students’ learning motivation. If the family environment is not good and not espouse so the students’ learning motivation decreases.Keywords: Family Environment, Learning Motivation